Apostolic Roots of Syro-Malabar Liturgy: The first Apostolic Proclamations and the Thomistic Christ-Experience in the Syro-Malabar Liturgy - Kureethara , Joseph Varghese (Asian Horizons, 2011)
Naiju Jose Kalambukattu, Apostolic Roots of Syro-Malabar Liturgy: The first Apostolic Proclamations and the Thomistic Christ-Experience in the Syro-Malabar Liturgy, Bangalore: Dharmaram Publications, 2011. Pages: xiv+168. ISBN 978-81-89958-43-5.